2016
DOI: 10.1016/j.drugalcdep.2016.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-related blackouts across 55 weeks of college: Effects of European-American ethnicity, female sex, and low level of response to alcohol

Abstract: Background While high blood alcohol concentrations (BACs) are required for alcohol-related blackouts (ARBs), additional characteristics also contribute to the risk, including a person’s ethnicity, sex, and phenotypes relating to heavier drinking. Few prospective studies of ARBs have evaluated how these additional characteristics interact. Method Data regarding 398 European American (EA), Asian and Hispanic students were extracted from a 55-week prospective study of different approaches to decrease heavy drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Our findings are consistent with prior work that subjective responses to alcohol are associated with experiencing blackouts (Schuckit, Smith, Goncalves, et al, 2016; Wetherill & Fromme, 2009). Having controlled for the quantity of drinking, our results suggest there is something unique about the sensitivity to feelings of intoxication that increases the likelihood of experiencing blackouts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with prior work that subjective responses to alcohol are associated with experiencing blackouts (Schuckit, Smith, Goncalves, et al, 2016; Wetherill & Fromme, 2009). Having controlled for the quantity of drinking, our results suggest there is something unique about the sensitivity to feelings of intoxication that increases the likelihood of experiencing blackouts.…”
Section: Discussionsupporting
confidence: 92%
“…Despite this, the highest rates of alcohol-related problems occur in this age group, making this an important developmental phase to study. We also used single items to assess blackouts, subjective intoxication, and motivation to change; however, single items have been used previously for blackouts (Schuckit et al, 2015; Schuckit, Smith, Shafir, et al, 2016; Schuckit, Smith, Goncalves, et al, 2016), subjective intoxication (Quinn & Fromme, 2012), and motivation to change (Chung, Pajtek, & Clark, 2013; Morgenstern et al, 2016). Finally, our model only allowed us to examine three years of data because our expanded definition of blackouts was not added until the Year 4 survey.…”
Section: Discussionmentioning
confidence: 99%
“…While gender was not significantly associated with endorsement of amnesia (the primary moderator) or alcohol-related consequences (the primary dependent variable), gender differences in rates of alcohol metabolism and, potentially, neurobiological vulnerability to alcohol may lead to differential rates of alcohol-induced amnesia among women and men (Mumenthaler, Taylor, O’Hara, & Yesavage, 1999; Sharret-Field et al, 2013). While some research has failed to find gender differences in rates of alcohol-induced amnesia (Marino & Fromme, 2015; Merrill et al, 2016; Mundt et al, 2012), other research has found gender differences (Schuckit, Smith, Goncalves, & Anthenelli, 2016). Gender was included as a covariate in the models detailed in this manuscript; however, future studies examining gender differences in the association between alcohol-induced amnesia and consequences are encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Low LRs can be determined through alcohol challenges where individuals carrying an elevated risk of alcohol problems and appropriate controls are given alcohol and the intensity of responses over time is observed regarding subjective feelings of intoxication as well as alcohol‐related changes in physiological measures (e.g., Ehlers et al., ; King et al., ; Paulus et al., ; Schuckit and Gold, ; Schuckit et al., ). Alcohol challenge–based LR values have been reliably shown to relate to future heavier drinking, alcohol problems, and alcohol use disorders (AUDs) (Schuckit and Smith, ; Schuckit et al., ).…”
mentioning
confidence: 99%
“…Examples of significant positive correlations between SRE scores and future heavier alcohol intake and alcohol problems include data from the San Diego Prospective Study (SDPS), the Collaborative Study of the Genetics of Alcoholism (COGA), the U.K.‐based Avon Longitudinal Study of Parents and Children (ALSPAC), and others (e.g., Chung and Martin, ; Goncalves et al., ,b; Schuckit and Smith, ; Schuckit et al., , ). SRE‐based LR values are higher in men than women (i.e., men have a low LR per drink) (Eng et al., ; Schuckit et al., , , , ) and European Americans (EAs) compared to African Americans (AAs) and Asian individuals (Luczak et al., , ; Park et al., ; Pedersen and McCarthy, ). However, within each sex and ethnic/racial group low LR values (higher SRE scores) correlate with heavier drinking and alcohol problems (e.g., Schuckit et al., , ,b).…”
mentioning
confidence: 99%